Diabetes mellitus and pregnancy: clinical cases from the practice of an endocrinologist - T. N. Markova; Ya. A. Solovyeva; A. V. Pechenkina; A. V. Gorshkova (Лечащий Врач, 2021)
According to the annual increase in the number of patients with diabetes worldwide, the number of women of reproductive age with disorders of carbohydrate metabolism (DMC) is increasing also. The increase in the prevalence of DMC in pregnancy is due to a change in diagnostic criteria since 2012 and an increase in the number of patients with obesity, as well as an improvement in the quality of diagnosis. The diagnostic difficulties with DMC are caused by clear clinical signs and low hyperglycemia in gestational diabetes mellitus (GDM) have been detected late. As a screening method for diagnosing possible DMC in pregnant women during pregnancy, an oral glucose-tolerant test is carried out. GDM is a serious medical and social problem. It is one of the most frequent extragenital pathologies of pregnancy, which increases the number of complicated outcomes for both the mother and the fetus, and subsequently negatively affects the development of the newborn. In patients with diabetes mellitus (DM) and prediabetes, complications during of the pre- and post-gravidar periods, as well as abnormalities of fetal growth and development are most frequent. Complications of the fetus from the mother with DMC can be divided into two groups: diabetic embriopathy and diabetic fetopathy. Nowadays, the most obvious point is the prevention of complications of DMC during gestation. Planning and management of pregestational DM in pregnancy control plays a major role in preventing risks, both for the mother and for the fetus, and is the basis for the birth of a healthy baby. The study reports clinical cases of pre-gestational and manifest diabetes in pregnancy.